The Investigate The Impact of Locus of Control and Self-Confidence on Prosocial Behavior and Religiosity among Students - Fatimah Saguni; Hatta Fakhrurrozi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
The goal of this study was to see what effect locus of control and self-confidence had on the prosocial behavior and religiosity of students at State Islamic University Datokarama. The methodology employed was quantitative. The data was analyzed using multiple linear regression correlation, which was done with SPSS for Windows version 17. This study covered four variables, consisting of two independent variables and two dependent variables, namely locus of control (X1) and self-confidence (X2) as independent factors and prosocial behavior (Y1) and religiosity (Y2) as dependent variables, with a total of 30 students as samples. The Likert scale was utilized as the instrument or data-gathering tool by the researcher. (1) Locus of control has a considerable effect on IAIN Palu students' prosocial conduct. People with an internal locus of control contributed to their competency by exercising environmental control. (2) The locus of control variable had a substantial effect on IAIN Palu students' religiosity. The man diligently followed his religious teachings and commitments. (3) The self-confidence variable had a substantial effect on IAIN Palu students' prosocial conduct. Prosocial behavior is defined as behavior that demonstrates a student's concern and attention through acts that help others. (4) The self-confidence variable had a substantial effect on IAIN Palu students' religiosity. Their acts were free of concern. They were free to do anything they wanted, were accountable for their acts, and were courteous in their relationships with others.